PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA BERDASARKAN PP. NO 50 TAHUN 2012 DI PT. PLN (PERSERO) UNIT INDUK TRANSMISI JAWA BAGIAN BARAT TAHUN 2021 - Bintang Ramadhania (2022)
Occupational Safety and Health is abbreviated as K3 which means providing a protection value to workers from work accidents or Occupational Diseases. SMK3 is a management system in an effort to control risks related to work processes in order to make the workplace safe. The purpose of this study was to determine the application of SMK3 based on PP. No. 50 of 2012 at PT. PLN (Persero) UIT JBB This research is qualitative with a descriptive approach with the number of informants 4 workers at PT. PLN (Persero) UIT JBB. The informant selection technique in this study was carried out by purposive sampling. The results of this study indicate the assessment of the application of SMK3 at PT (PLN) UIT JBB in the advanced level category, which is 91.57%, and is included in the satisfactory category. Therefore, the researcher suggests PT.PLN UIT JBB to periodically review K3 policies, rearrange the budget in order to renew the licenses of emergency handling officers, provide competent officers to monitor the work environment for ergonomic factors and immediately follow up up to the results of the work environment monitoring analysis for psychological factors so that they can be used for risk assessment and control.